The development of integrated thematic textbooks with scientific approach for elementary schools students - Winda Elvita; Risda Amini; Riska Ahmad (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
The preliminary survey in Elementary School in Lima Puluh Kota District showed that the textbook for thematic learning was not in accordance with the principles of integrated learning and not yet in accordance with the around environment of the students, so that the lesson was not understood of the students. therefore the purpose of this study is to develop integrated thematic textbooks using the scientific approach valid, practical and effective.The research used the four D model of Tiagahajan that consist of 4 stages, namely: define, design, develop, and disseminate. The research instruments were observation sheets, validation sheets, questionnaires, learning outcomes tests. The results showed that integrated thematic textbooks with a scientific approach include valid categories based on expert judgment. Textbooks include very practical categories based on teacher and student responses. Effectiveness of textbooks based on student learning activities and mastery learning. The most of students were active in learning. The student learning outcome in the knowledge, skills, and attitudes domain has been include the mastery learning category for the most of students (more than 85%). Thus it can be concluded that integrated thematic textbooks with scientific approaches were feasibility of being used as reference books in Elementary School.